2012
DOI: 10.2139/ssrn.2084609
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Private Incidence of Corruption and Firm Ownership on Performance of Firms in Central and Eastern Europe

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Corruption is perceived as a major hurdle for regional investment and business efficiency (EUROCHAMBRES, 2009). The average frequency of informal payments in 2009 was around two in the observed Western Balkan countries, as reported in BEEPS (Blagojević and Damijan, 2011). Corruption is a primary obstacle faced by business establishments in Kosovo (according to 21% of respondents), and is considered a significant factor in Croatia (9%), Albania and Bosnia and Herzegovina (8%), Serbia (7%), and Montenegro (6%).…”
Section: Institutional Context For Assessing Corruption In the Western Balkanssupporting
confidence: 57%
“…Corruption is perceived as a major hurdle for regional investment and business efficiency (EUROCHAMBRES, 2009). The average frequency of informal payments in 2009 was around two in the observed Western Balkan countries, as reported in BEEPS (Blagojević and Damijan, 2011). Corruption is a primary obstacle faced by business establishments in Kosovo (according to 21% of respondents), and is considered a significant factor in Croatia (9%), Albania and Bosnia and Herzegovina (8%), Serbia (7%), and Montenegro (6%).…”
Section: Institutional Context For Assessing Corruption In the Western Balkanssupporting
confidence: 57%
“…Vial and Hanoteau (2010) found that corruption is associated with an increase in firm output and productivity. Blagojevic and Damijan (2012) found that private firms that are involved in making corrupt payments to public officials have higher productivity than firms that do not make payments.…”
Section: Corrupt Practices Will Results In An Increase In Firm Growthmentioning
confidence: 99%
“…In a Turkish study, Ayaydin and Hayaloglu (2014) found that manufacturing firms that are involved in making corrupt payments to public officials had increased growth. Blagojevic and Damijan (2012) concluded that private firms that offer bribes to public officials will have higher productivity than those that do not offer bribes. Our findings suggest that the need to mitigate the corruption obstacle in MSMEs appears to be a rational economic choice that often benefits MSMEs.…”
Section: Discussionmentioning
confidence: 99%
“…However, in comparison to older EU member states, new European member states with lower GDP are more prone to corruption, this phenomenon affecting economic wealth to a greater extent. The main reason for this divergence in comparison with the OMS resides in the institutional quality, as well as in the historical background, of NMS in terms of democracy, culture and population education, and trust in the state apparatus, as concluded by Blagojevic and Damijan [58] and Bakowski and Varonova [59]. As stated by Van Der Hoek [60], high levels of corruption expose enterprises and businesses to additional risks, and have a burdensome impact on economic growth, especially in the new post-communist member countries.…”
Section: Discussionmentioning
confidence: 99%